Application of tax avoidance and company size in influencing company value in the food and beverage sector - Rizki, Irma Herliza; Syahputra, Oky; Masri, Debi; Rinaldi, Muammar (International Journal of Applied Finance and Business Studies, 2024)
Previous research objectives discuss How profitability effective in tax body income, however In this research the author saw tax avoidance effectiveness and size company in influence Company value in the sector manufacture food and Drink. Next research will be refers application mark company in growth economy. The research method uses quantitative data sourced from the Indonesian Stock Exchange (BEI). The population will used In this research there were 26 companies manufacturing sub sector food and beverages listed on the Indonesian Stock Exchange. Retrieval technique sample in this research is a purposive sampling technique. Then analyzed using analysis multiple linear regression, according to terms and conditions statistics. The results of this research are that the variables Tax Avoidance and Company Size have an influence significant on the company's corporate value manufacture subsector food and beverages listed on the Indonesian Stock Exchange means the more tall level debt and legal Company Value treatment will give positive impact​ for investors. This is stated hypothesis third (H3) which states The influence of Tax Avoidance and Company Size on Company Value is accepted.